The Role of Management Information System Innovation as a Catalyst to Enhance Profitability in the Contemporary Digital Business Era - Muhamad Malik Mutoffar; Achirsyah Bahar; Fahrina Mustafa (Politeknik Ganesha Medan, 2024)
Digital business has become a phenomenon dominating the global market, influencing various industries, and changing the way companies operate and interact with customers. This research aims to examine the crucial role of innovation in MIS as a catalyst for enhancing profitability in digital businesses. The research method employed is a qualitative literature review conducted by gathering data from Google Scholar within the timeframe of 2003 to 2024. The study findings indicate that innovation in management information systems (MIS) plays a vital role in enhancing profitability in digital businesses in the contemporary era. Through the implementation of advanced information technology, businesses can create added value, improve operational efficiency, and respond to market changes more quickly. Innovation in MIS also enables the development of new business models, enhances customer experiences, and creates a more sustainable business environment.